PENGARUH KEPEMIMPINAN DEMOKRATIS, BEBAN KERJA DAN STRESS KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. JEJE INTI GROUP KABUPATEN KONAWE UTARA - Jefri, Jefri; Kalsum, Ummy; Putera, Asrip (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine and analyze the effects of democratic leadership, workload, and job stress on employee turnover intention at PT. Jeje Inti Group, North Konawe District. The sample consisted of all 35 employees at PT. Jeje Inti Group, North Konawe District. The study employed Multiple Linear Regression analysis. The research findings indicate that: (1) Democratic leadership, workload, and job stress have a positive and significant impact on employee turnover intention at PT. Jeje Inti Group, North Konawe District. (2) Democratic leadership has a negative and insignificant impact on employee turnover intention at PT. Jeje Inti Group, North Konawe District. (3) Workload has a positive and significant impact on employee turnover intention at PT. Jeje Inti Group, North Konawe District. (4) Job stress has a positive and significant impact on employee turnover intention at PT. Jeje Inti Group, North Konawe District.